Business process improvement for internal quality assurance using information systems: A case study of a vocational higher education institution - Nina Fadilah Najwa; Istianah Muslim; Heni Rachmawati (Jurnal Pendidikan Vokasi, 2026)
Digital transformation in higher education institutions (HEIs) requires not only the adoption of technology but also a clear roadmap for successful implementation and effective change management. As independently funded institutions, private HEIs must also consider their strategic and operational business needs. This study aims to identify and analyze business process improvements in the governance of the Internal Quality Assurance System (Sistem Penjaminan Mutu Internal/SPMI) through a single case study of a private vocational HEI in Indonesia. The research consisted of a literature review, identification of primary and supporting business processes, focus group discussions (FGDs), and value chain analysis. Business process improvement was conducted through five stages: organizing for improvement, understanding the process, streamlining, measuring and controlling, and continuous improvement. Business Process Model and Notation (BPMN) was used to model and visualize the redesigned business processes. The findings produced a comprehensive blueprint of the internal quality assurance process and the SPMI business process cycle for vocational HEIs. The redesigned process addresses a critical gap in the previous system by strengthening the linkage between evaluation and control outcomes and institutional policy formulation. The improved SPMI cycle is more structured and efficient through refinements to the audit process, the application of Eisenhower Matrix analysis, and the management of indicator duplication. In addition, the study developed a real-time e-SPMI dashboard and a base-indicator detection feature to minimize indicator duplication. This study contributes theoretically by integrating the SPMI literature with a business process improvement perspective and extending value chain analysis within internal quality assurance. Practically, it provides a BPMN-based process model and value chain framework that can be directly implemented at Politeknik Caltex Riau (PCR) and adapted by other private vocational HEIs with similar organizational contexts.